1970
DOI: 10.1104/pp.46.4.527
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Pattern of Photosynthate Movement within and between Shoots of Vitis vinifera L

Abstract: During the prebloom and bloom stages, no movement of labeled photosynthates occurred from a shoot of Vitis vinifera L. fed with 14CO2, to an adjacent shoot on the same spur.Movement of labeled assimilates into the unfed shoot was induced when this shoot was sprayed with 2.89 X 1O-3 The distribution of photosynthetic products from single leaves on shoots of Vitis vinifera L. has been described previously (2). During the period of shoot growth, the direction of photosynthate movement from a given source leaf c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
3

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 6 publications
1
22
0
3
Order By: Relevance
“…Quinlan and Weaver (1970) found that downward movement of photosynthate in Vitis vinifera L. could be reversed by darkening the upper portion of the shoot. Thrower and Thrower (1980) Schneider and Eschrich 1985).…”
Section: Discussionmentioning
confidence: 98%
“…Quinlan and Weaver (1970) found that downward movement of photosynthate in Vitis vinifera L. could be reversed by darkening the upper portion of the shoot. Thrower and Thrower (1980) Schneider and Eschrich 1985).…”
Section: Discussionmentioning
confidence: 98%
“…While the relationships between photoassimilated carbon and carbon supply to the fruit have been extensively studied in grapevines (Hale and Weaver 1962;Koblet 1969Koblet , 1975Quinlan and Weaver 1970;Koblet and Perret 1972, 1979, 1982Stoev and Ivantchev 1977;Hunter and Visser 1988a, b;Motomura 1981Motomura , 1990), information on the retranslocation of carbohydrates stored in the permanent structure of the vine is limited to the fate of the carbon reserves accumulated in the previous growing season. Scholefield et al (1978), Hori (1979, 1980) and studied the contribution of assimilates accumulated in the previous (long-term reserves) and current season (daily reserves) to early shoot growth of grapevine.…”
Section: Introductionmentioning
confidence: 99%
“…2. Allocation time partições apicais no menor tempo estudado (Quinlan & Weaver, 1970;Quinlan & Preston, 1971;Simkhada et al, 2007).…”
Section: Resultsunclassified